AS POLÍTICAS PÚBLICAS CULTURAIS NO CONTEXTO PANDÊMICO: uma análise comparativa entre Brasil e América Latina - Mariana de Araujo Aguiar; Luciana de Araujo Aguiar (Revista de Políticas Públicas, 2021)
This paper aims to analyze the actions of the Brazilian government in relation to other Latin American countries (Chile, Peru, Argentina and Cuba), especially in regard to emergency policies for the cultural sector during the first six months of the COVID-19 pandemic. The research was based on analyzes of legal instruments, communication channels and bibliographic analysis. From the study, it was found that, despite different forms of state and political issues, the countries surveyed, with the exception of Brazil, had effective action by the ministries of culture to coordinate and promote emergency actions in the first half of 2020.